Ultrasound Neuromodulation of the Spleen Has Time-Dependent Anti-Inflammatory Effect in a Pneumonia Model - Ahmed, Umair; Graf, John F.; Daytz, Anna; Yaipen, Omar; Mughrabi, Ibrahim; Jayaprakash, Naveen; Cotero, Victoria; Morton, Christine; Deutschman, Clifford Scott; Zanos, Stavros; Puleo, Chris (Frontiers in Immunology, 2022)
Recently interfaces between the nervous and immune systems have been shown essential for the coordination and regulation of immune function. One such interface in the spleen, the cholinergic anti-inflammatory pathway (CAP), has been well-studied and shown to control peripheral cytokine levels and inflammation. Over the past decade this neuro-immune pathway has been activated pharmacologically or using nerve stimulators and studied in animal models and clinical studies. However, these CAP investigations have typically been performed in models or study populations of severe/systemic (e.g., endotoxemia) or pathological (e.g., collagen-induced arthritis or DSS-induced colitis) inflammation. Herein, we examine the effects of stimulating CAP in a model of local bacterial infection (i.e., lung instillation of low challenge dose pathogenic bacteria). Unlike previous reports, we demonstrate a time-dependent effect of CAP stimulation on peripheral cytokine response during progression of the infection. That is, cytokine suppression was not observed following CAP stimulation during intermediate phases (i.e., 16 hours following inoculation) of infection, but was shown during the acute phase (i.e., 4 hours) and at resolution (i.e., 48 hours). These results demonstrate cholinergic anti-inflammatory pathway activity during infection, and highlight the importance of further studying nervous and immune system interfaces in the context of different immune system/inflammatory states.